The effect of darkness on mating and pleopodal egg production time in a freshwater crayfish, Astacus leptodactylus Eschscholtz - Harlioglu, Muzaffer Mustafa; Duran, Tuba Cakmak (Springer, 2010)
In the present study, the effect of darkness on the timing of mating and pleopodal egg production in Astacus leptodactylus was investigated. Crayfish were exposed to three different light regimes: natural day light regime (control, mean 10.04-h light/13.96-h dark); 24-h dark (24 h D); 8-h light/16-h dark (8 L:16 D). Experiments were carried out between November 2006 and January 2007 with 36 males and 144 females. The results showed that darkness did not have an effect on the onset of mating and pleopodal egg production in the groups, but it did affect significantly the timing of individual matings; the higher percentage of ovigerous females in the darkness group at the first observation means that on average females under this condition mated and spawned earlier than in the other groups (P < 0.01). The percentage of ovigerous females exposed to constant darkness in the first observation in which crayfish started to mate and spawn was 62.50. These figures for those exposed to 16 D:8 L and control were 43.75 and 37.50%, respectively. Therefore, it can be concluded that the reproduction efficiency (i.e., rate of ovigerous females) of A. leptodactylus can be enhanced under controlled conditions by exposing broodstock to constant darkness in their mating and spawning season.
Keywords: Freshwater crayfish; Astacus leptodactylus; Light; Mating; Pleopodal egg production; Darkness